2014
DOI: 10.1007/s10120-014-0393-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer in patients with type I gastric carcinoids

Abstract: Background Atrophic body gastritis (ABG) is associated with both type I gastric carcinoids (T1-GCs) and intestinaltype gastric cancer. The occurrence of gastric cancer in ABG patients with type I gastric carcinoids has not yet been described. Aim To describe the occurrence at follow-up of gastric cancer in ABG patients with type I gastric carcinoid in a retrospective case series in a single tertiary referral center. Methods Between 1994 and 2012, 17 new cases of T1-GCs were diagnosed among a cohort of ABG pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…In 2004, Lahner et al published the first study regarding the occurrence of gastric cancer and type 1 carcinoid in patients with atrophic body gastritis [28]. In case 2 of our study, the presence of adenoma/HGD and NET G1 in the stomach was found.…”
Section: Discussionsupporting
confidence: 52%
“…In 2004, Lahner et al published the first study regarding the occurrence of gastric cancer and type 1 carcinoid in patients with atrophic body gastritis [28]. In case 2 of our study, the presence of adenoma/HGD and NET G1 in the stomach was found.…”
Section: Discussionsupporting
confidence: 52%
“…So far, the presented data constrain that repeated local resections by short and mid-term endoscopic follow-up is a pragmatic and cost-effective approach which leads to a very good clinical outcome of gNEN-1, even in cases of recurrence or progression due to ongoing HG caused by CAG. However, follow-up intervals are part of ongoing controversy, probably because of inconsistent reports on the adenocancerogenic potential of CAG and intestinal metaplasia itself (Chen et al 2015, Lahner et al 2015, Xie et al 2017). Neither adenocarcinoma nor a life-threatening progression of gNEN-1 was documented during follow-up in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer and NET lesions are reportedly observed in 0.9-9% and 4-9% of patients with autoimmune gastritis, respectively (14). The pathogenesis of gastric cancer is attributed to atrophic gastritis resulting in intestinal metaplasia (2) or long-term hypergastrinemia (15), leading to the development of adenocarcinoma, while that of type I gastric NET is attributed to elevated gastrin secretion in response to the loss of negative feedback by parietal cells, wherein hypo-/achlorhydria-induced hypergastrinemia results in enterochromaffin-like (ECL) cell hyperplasia and dysplasia, thus leading to type I gastric NET (16, 17). In our case, the patient was shown to be positive for anti-parietal cells, anti-intrinsic factor antibodies, and hypergastrinemia (gastrin, up to 1,440 pg/mL) but negative for serum H. pylori IgG antibody.…”
Section: Discussionmentioning
confidence: 99%